Estudio de prefactibilidad para la instalación de una planta productora de harina a base de sub-productos del proceso industrial de café (Coffea) - Peña Muguruza, Luz Gabriela (2020)
The following study presents the required aspects to demonstrate the viability of an installation of a processing plant of flour obtained by the use of byproducts of coffee located in Moyobamba in San Martín, for direct consumer sale. In the next we will show a summary of the results found in which it is demonstrated that this project is viable economically, technically, socially and environmentally. The target market is the population of Lima that belongs to the socioeconomic levels A, and B between the ages of 18 and 55. Through 384 surveys we determined both customer purchase intention and intensity. That helped with the estimation of the demand of the project, that will be 1,383 TN the last year. The location of the plant was determined through macro and micro location analysis defining and evaluating different factors including availability of raw material, availability of land, proximity to the target market, water and energy supply, among others. Finally, using the factor ranking method, the most appropriate location to install the plant would be Moyobamba in San Martín. To determine the capacity of the production plant delimiting factors were established such as market, technology, raw material and labor which it was concluded that the Project size would be delimited by the market with 1, 383,900 kg per year. Regarding the production process, it was determined that the plant capacity was 2’659,595 kg / año. Finally, we obtained that the project is economically and financially viable because of the positive NPV (S/.4’262,698 and S/.4’442,395); the eIRR of 46.67% and fIRR of 57.51%; and P/C ratio of 2.11 and 2.652.